Penggunaan Media Sosial Hubungannya dengan Pengetahuan Etika Komunikasi Islam dan Prestasi Belajar PAI - Aprilia Nurhida; Arih Merdekasari (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2019)
The study is a correlation study. Sampling uses purposive random sampling technique with the criteria of students aged 16-19 years. The number of sampel are 51 students in class X and XI SMA Muhammadiyah 1 Ngawi. Data collection instruments are; social media use scale, islamic communication ethics knowledge test and Raport of PAI. Data analysis through Bivariate Correlation shows that there is no correlation between social media use with the Islamic communication ethics knowledge and academic achievement in PAI. More deeply there are findings of correlation between Islamic communication ethics knowledge and aspects of social media use in social interaction and relaxation